The stuctural heart in the arabic language a morphosyntanctic and semantic study - Karim, Asst.Prof.Dr. Zana Shabaz Karim (Sulaimani Journal for Humanities, 2025)
This research is an attempt to study a structural phenomenon in the Arabic language represented in the reversal of grammatical functions between the elements of the structure, such as making the subject or the agent's deputy an object, making the object an agent or agent's deputy, or making the agent in meaning a noun in the genitive case, and making the genitive case an agent. This prompted the researcher to name the phenomenon (structural reversal). The research works to highlight this linguistic phenomenon in the Arabic language in light of the poetic evidence and various examples cited by lexicographers and grammarians in their writings. The research analyzes this phenomenon structurally, and attempts to uncover the underlying reasons behind its existence in the Arabic language.